Informed consent in international research: perspectives from India, Iran and Nigeria (2006)
The amount of international biomedical research is increasing and much of this is happening in developing countries. It is important to place adequate focus on the issue of obtaining voluntary informed consent. Researchers need to understand local socio-cultural realities and also respect local cultural beliefs and indigenous research guidelines. Through examples from India, Iran and Nigeria the authors highlight the diversity within and between developing country situations. Emphasis is placed on the importance of informed consent in research as well as clinical practice settings, and the need to be enterprising and innovative in obtaining it.